Historische Textmuster im Wandel. Neue Wege zu ihrer Erschließung

Kollegiale Kooperation im Lehrer:innenberuf. - Kullmann, Harry (Beruf Lehrer:in. Ein Studienbuch (2. Auflage))

Gebaute Heiligung. Wie Stadtumbau und Heiligenverehrung des späten 17. und frühen 18. Jahrhunderts Paderborn in eine heilige Stadt verwandelten - Süßmann, Johannes ((Un)verfügbar – Kulturen des Heiligen)
Nach dem Dreißigjährigen Krieg kam es in Paderborn zu einem Stadtumbau. Unter der Regierung des Fürstbischofs Ferdinand von Fürstenberg (1661–1683) wurden drei neue Kirchen errichtet, eine ältere erhielt eine neue Fassade. Das machte alle vier zu städtebaulichen Dominanten – nicht nur durch Größe und Positionierung, sondern weil sie die Barockfassade in Paderborn einführten und damit die Kirchen in ein neues Verhältnis zum städtischen Raum rückten. Gestaltet als Schaufronten vor bühnenartigen Vorplätzen, trugen die Fassaden dazu bei, die vorher auf die Innenräume beschränkte Heiligenverehrung in den Stadtraum hinaus zu wenden und auch im Alltag vor Augen zu stellen. Zugleich wurde ein neuer Prozessionsweg geschaffen, der die Verehrung aller Kirchenpatrone zusammenführte und zu einer Aufgabe für die gesamte Stadt machte. Über Wallfahrtskapellen bezog man das Umland mit ein. Das gesamte Fürstbistum wurde geheiligt. Der politische Sinn war, es nach den Erschütterungen des Dreißigjährigen Kriegs im Innern neu zu begründen und nach außen sakrosankt zu machen.

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

Oh my Goodness: Investigating the Goodness of Performance Appraisal Formats Between and Within Teams - Gutt, Jana Kim; Mehic, Miro; Thommes, Kirsten (Academy of Management Proceedings)

Hitting the Breaks While Working from Home. Changes in Taking-Breaks Behaviours During Pandemic Lockdowns - Voicu, Bogdan; Țălnar-Naghi, Dana; Neguț, Adriana; Glăvan, Eugen; Tufă, Laura; Florea, Alexandra (Sociológia - Slovak Sociological Review)
Keywords: Sociology and Political Science

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Müttertragödien. Affekt, Macht und Politik in Marie-Anne Barbiers 'Cornélie, mère des Gracques' (1703) - Steigerwald, Jörn (Romanistische Zeitschrift für Literaturgeschichte)

Molière, dramaturge de la société de cour. - Steigerwald, Jörn; Schlieper, Hendrik

Entwicklung und Analyse von Formeln zur Abschätzung der Renderingzeit eines Frames - Nickel, Alexander

Reconstruction of 3D Surfels from Neural Radiance Fields - Telaprolu, Vipasyan

Shape Reconfiguration by Hybrid Programmable Matter - Friemel, Jonas

Les trois corps du roi ou la comédie familiale de Molière: "La Princesse d'Élide" - Steigerwald, Jörn (Molière, dramaturge de la société de cour)

TCO analysis of a modular and integral product architecture in shipbuilding - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Wicker, Ansgar; Dumitrescu, Roman; Tolo, Edmund

Charles Perraults 'Le Siècle de Louis le Grand' oder die Erfindung von Traditionen - Steigerwald, Jörn (Zeiten bezeichnen. Frühneuzeitliche Epochenbegriffe: europäische Geschichte und globale Gegenwart)

Future production of ships – case study for modular high-speed ferries - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman

Schlaffer Rückzug. Michel Houellebecqs 'Soumission' - Steigerwald, Jörn (Elan und Müdigkeit. Zwischen Spannkraft und Entspannung. Literarische Figurationen und anthropologischer Diskurs)

Illustrationen musikalischen Vergnügens. Die Bildrhetorik des 'Grand Divertissement royal' (1668) - Steigerwald, Jörn (Musik im Blick. Visuelle Perspektiven auf auditive Kulturen)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Fautes donjuanesques, remontrances galantes. Réflexions sur Le Festin de Pierre de Molière - Schlieper, Hendrik (Molière, dramaturge de la société de cour)

Idélic Approach in Enumerating Heisenberg Extensions - Klüners, Jürgen; Wang, Jiuya (La Matematica)

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Ursachen vorzeitiger Vertragslösungen im Spannungsfeld von statistischer Beschreibung und Praxis - Heisler, Dietmar; Lüttke, Daniela (Berufsbildung)

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Apocalypse Now? Endzeitphantasmen bei Wilhelm Genazino und Markus Orths - Süwolto, Leonie (Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren ‚Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller‘)

Kormart, Christoph - Süwolto, Leonie (Frühe Neuzeit in Deutschland 1620-1720. Literaturwissenschaftliches Verfasserlexikon, Band 4: Hellwig, Christoph von – Lebaldt von Lebenwaldt, Adam)

Drama I: Das Projekt der Deutschen Schaubühne - Süwolto, Leonie (Gottsched-Handbuch. Leben – Werk – Wirkung)

Show me the verb: Visualisierung von Wortstellungsregeln im DaF-Unterricht für die Grundstufe - Lentfort, Theresa; Mentchen, Silke (GfL)
Die charakteristische Verbzweitstellung des Deutschen und die sogenannte Satzklammer führen bei der Sprachproduktion vieler Lernender zu klassischen Fehlern und Frustration. Die Herausforderung für den fremdsprachlichen A1-/A2-Unterricht besteht darin, das Phänomen der Verbstellung didaktisch so zu reduzieren, dass der Gegenstand zwar nicht unzulässig vereinfacht wird, die DaF-Lernenden aber ein leicht handhabbares Modell für die Sprachproduktion zur Verfügung haben, das sie auch ohne umfassende linguistische Vorkenntnisse nutzen können. Im vorliegenden Beitrag werden wir zeigen, wie eine Vermittlung dieses grammatischen Inhalts durch Metaphorisierung und Visualisierung gelingen kann. Dazu untersuchen wir gängige Metaphern, die in Lehrmaterial für A1-/A2-Niveau zur Einführung der Verbzweitstellung und der Klammerstruktur verwendet werden, und geben einen Überblick über die dort eingesetzten Visualisierungen, deren didaktischen Nutzen wir anhand eines von uns erstellten Kriterienkatalogs analysieren. Hierzu fassen wir syntaktische Modelle wie das Feldermodell, die Dependenz- und die Valenztheorie im Kontext unseres Interesses zusammen. Ziel unserer Untersuchung ist es, brauchbare und ausbaufähige Modelle zu identifizieren.
Keywords: A1-/A2-Unterricht; Verbstellung; Satzklammer; Metapher; Visualisierung; Lerntheorie; Kognitive Linguistik; Lehrmaterial

Action outcome probability influences the size of the head-fake effect in basketball - Güldenpenning, Iris; Jackson, Robin C.; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

RISE: an open-source architecture for interdisciplinary and reproducible human–robot interaction research - Groß, André; Schütze, Christian; Brandt, Mara; Wrede, Britta; Richter, Birte (Frontiers in Robotics and AI)
In this article, we present RISE—a R obotics I ntegration and S cenario-Management E xtensible-Architecture—for designing human–robot dialogs and conducting Human–Robot Interaction (HRI) studies. In current HRI research, interdisciplinarity in the creation and implementation of interaction studies is becoming increasingly important. In addition, there is a lack of reproducibility of the research results. With the presented open-source architecture, we aim to address these two topics. Therefore, we discuss the advantages and disadvantages of various existing tools from different sub-fields within robotics. Requirements for an architecture can be derived from this overview of the literature, which 1) supports interdisciplinary research, 2) allows reproducibility of the research, and 3) is accessible to other researchers in the field of HRI. With our architecture, we tackle these requirements by providing a Graphical User Interface which explains the robot behavior and allows introspection into the current state of the dialog. Additionally, it offers controlling possibilities to easily conduct Wizard of Oz studies. To achieve transparency, the dialog is modeled explicitly, and the robot behavior can be configured. Furthermore, the modular architecture offers an interface for external features and sensors and is expandable to new robots and modalities.
Keywords: Artificial Intelligence; Computer Science Applications

Bilder vor unseren Augen – Bilder in unseren Köpfen. Stereotype und Geschichte - Hansen, Christin (Sieh dir die Menschen an! Das neusachliche Typenporträt in der Weimarer Zeit)

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Sprachlichkeit des Geschichtslernens. Fachliche Grundlagen, Sprachgebrauch und Ansätze fachintegrierter Spracharbeit - Hartung, Olaf (Beiträge zur Lehrerinnen- und Lehrerbildung)

Pazifizierende Toleranz. Wolmar und die Domestizierung der Affekte in Rousseaus Nouvelle Héloïse - Schlieper, Hendrik (Literaturwissenschaftliches Jahrbuch)
Keywords: Literature and Literary Theory

Lunchables. Über den Zusammenhang von Essen und Klasse - Hagemann, Philipp; Wagner, Alexander

Zum Stellenwert von Leibniz in Schulbüchern des Philosophie- und Ethikunterrichts - Hagemann, Philipp (Zeitschrift für Didaktik der Philosophie und Ethik)

Carbon insetting as a measure to raise supply chain energy efficiency potentials: Opportunities and challenges - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, Dennis; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Concept for a cloud-based holistic energy management of domestic appliances to stabilize the energy supply and the power grid - Stieren, Stephan; Wichtrup, Moritz; Henke, Christian; Trächtler, Ansgar (NEIS - Conference on Sustainable Energy Supply and Energy Storage Systems)

Rezension zu Gunther Wenz: Im Werden begriffen. Zur Lehre vom Menschen bei Pannenberg und Hegel. Pannenberg Studien 7, Göttingen: Vandenhoeck & Ruprecht 2021 - Meyer zu Hörste-Bührer, Raphaela (Theologische Literaturzeitschrift 2023/1)

Ethik in Beziehungen. Im Gespräch mit Hans-Joachim Höhns „Konturen einer Tugendethik“ - Meyer zu Hörste-Bührer, Raphaela (Gott – Welt – Mensch, Eine Auseinandersetzung mit Hans-Joachim Höhn)

On the Impact of Basic Mutation Operators and Populations within Evolutionary Algorithms for the Dynamic Weighted Traveling Salesperson Problem - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Evolutionary algorithms have been shown to obtain good solutions for complex optimization problems in static and dynamic environments. It is important to understand the behaviour of evolutionary algorithms for complex optimization problems that also involve dynamic and/or stochastic components in a systematic way in order to further increase their applicability to real-world problems. We investigate the node weighted traveling salesperson problem (W-TSP), which provides an abstraction of a wide range of weighted TSP problems, in dynamic settings. In the dynamic setting of the problem, items that have to be collected as part of a TSP tour change over time. We first present a dynamic setup for the dynamic W-TSP parameterized by different types of changes that are applied to the set of items to be collected when traversing the tour. Our first experimental investigations study the impact of such changes on resulting optimized tours in order to provide structural insights of optimization solutions. Afterwards, we investigate simple mutation-based evolutionary algorithms and study the impact of the mutation operators and the use of populations with dealing with the dynamic changes to the node weights of the problem.
Keywords: dynamic optimization; evolutionary algorithms; re-optimization; weighted traveling salesperson problem

Runtime Analysis of Quality Diversity Algorithms - Bossek, Jakob; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference)
Quality diversity (QD) is a branch of evolutionary computation that gained increasing interest in recent years. The Map-Elites QD approach defines a feature space, i.e., a partition of the search space, and stores the best solution for each cell of this space. We study a simple QD algorithm in the context of pseudo-Boolean optimisation on the "number of ones" feature space, where the ith cell stores the best solution amongst those with a number of ones in [(i - 1)k, ik - 1]. Here k is a granularity parameter 1 {$≤$} k {$≤$} n+1. We give a tight bound on the expected time until all cells are covered for arbitrary fitness functions and for all k and analyse the expected optimisation time of QD on OneMax and other problems whose structure aligns favourably with the feature space. On combinatorial problems we show that QD finds a (1 - 1/e)-approximation when maximising any monotone sub-modular function with a single uniform cardinality constraint efficiently. Defining the feature space as the number of connected components of a connected graph, we show that QD finds a minimum spanning tree in expected polynomial time.
Keywords: quality diversity; runtime analysis

Generating Diverse and Discriminatory Knapsack Instances by Searching for Novelty in Variable Dimensions of Feature-Space - Marrero, Alejandro; Segredo, Eduardo; Hart, Emma; Bossek, Jakob; Neumann, Aneta (Proceedings of the Genetic} and Evolutionary Computation Conference)
Generating new instances via evolutionary methods is commonly used to create new benchmarking data-sets, with a focus on attempting to cover an instance-space as completely as possible. Recent approaches have exploited Quality-Diversity methods to evolve sets of instances that are both diverse and discriminatory with respect to a portfolio of solvers, but these methods can be challenging when attempting to find diversity in a high-dimensional feature-space. We address this issue by training a model based on Principal Component Analysis on existing instances to create a low-dimension projection of the high-dimension feature-vectors, and then apply Novelty Search directly in the new low-dimension space. We conduct experiments to evolve diverse and discriminatory instances of Knapsack Problems, comparing the use of Novelty Search in the original feature-space to using Novelty Search in a low-dimensional projection, and repeat over a given set of dimensions. We find that the methods are complementary: if treated as an ensemble, they collectively provide increased coverage of the space. Specifically, searching for novelty in a low-dimension space contributes 56% of the filled regions of the space, while searching directly in the feature-space covers the remaining 44%.
Keywords: evolutionary computation; instance generation; instance-space analysis; knapsack problem; novelty search

Do Additional Target Points Speed Up Evolutionary Algorithms? - Bossek, Jakob; Sudholt, Dirk (Theoretical Computer Science)
Most runtime analyses of randomised search heuristics focus on the expected number of function evaluations to find a unique global optimum. We ask a fundamental question: if additional search points are declared optimal, or declared as desirable target points, do these additional optima speed up evolutionary algorithms? More formally, we analyse the expected hitting time of a target set OPT{$\cup$}S where S is a set of non-optimal search points and OPT is the set of optima and compare it to the expected hitting time of OPT. We show that the answer to our question depends on the number and placement of search points in S. For all black-box algorithms and all fitness functions with polynomial expected optimisation times we show that, if additional optima are placed randomly, even an exponential number of optima has a negligible effect on the expected optimisation time. Considering Hamming balls around all global optima gives an easier target for some algorithms and functions and can shift the phase transition with respect to offspring population sizes in the (1,{$λ$}) EA on OneMax. However, for the one-dimensional Ising model the time to reach Hamming balls of radius (1/2-{$ϵ$})n around optima does not reduce the asymptotic expected optimisation time in the worst case. Finally, on functions where search trajectories typically join in a single search point, turning one search point into an optimum drastically reduces the expected optimisation time.
Keywords: Evolutionary algorithms; pseudo-Boolean functions; runtime analysis

On Single-Objective Sub-Graph-Based Mutation for Solving the Bi-Objective Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (Evolutionary Computation)
We contribute to the efficient approximation of the Pareto-set for the classical NP-hard multi-objective minimum spanning tree problem (moMST) adopting evolutionary computation. More precisely, by building upon preliminary work, we analyse the neighborhood structure of Pareto-optimal spanning trees and design several highly biased sub-graph-based mutation operators founded on the gained insights. In a nutshell, these operators replace (un)connected sub-trees of candidate solutions with locally optimal sub-trees. The latter (biased) step is realized by applying Kruskal’s single-objective MST algorithm to a weighted sum scalarization of a sub-graph.We prove runtime complexity results for the introduced operators and investigate the desirable Pareto-beneficial property. This property states that mutants cannot be dominated by their parent. Moreover, we perform an extensive experimental benchmark study to showcase the operator’s practical suitability. Our results confirm that the subgraph based operators beat baseline algorithms from the literature even with severely restricted computational budget in terms of function evaluations on four different classes of complete graphs with different shapes of the Pareto-front.

Begriffliches Verständnis von Grundschüler*innen zur Achsensymmetrie - Wallner, Melina (Grundlegende Kompetenzen sichern: Lernende und Lehrende im Blick)
Dieser Tagungsband dokumentiert die Ergebnisse der 30. Jahrestagung des Arbeitskreises Grundschule in der Gesellschaft für Didaktik der Mathematik (GDM), die dieses Mal vom 17. bis zum 19. November 2023 an der Universität Bremen stattfand. Die Tagung stand unter dem Thema ‚Grundlegende Kompetenzen sichern: Lernende und Lehrende im Blick‘. Die Tagung greift damit die immer wieder aktuelle Frage auf, wie der Mathematikunterricht der Grundschule gestaltet werden kann, so dass alle Kinder grundlegende Kompetenzen erwerben und über diese auch sicher und langfristig verfügen. Empirische Studien wie etwa der IQB-Bildungstrend zeigen, dass der Anteil an Kindern, die diese Kompetenzen, die unbestritten für das Weiterlernen in den darauffolgenden Schuljahren und im Beruf relevant sind, am Ende ihrer Grundschulzeit (noch) nicht besitzen, größer wird. Weiter setzten sich acht Arbeitsgruppen mit den Themenfeldern ‚Arithmetik‘, ‚Geometrie‘, ‚Sachrechnen‘, ‚Daten, Zufall und Wahrscheinlichkeit‘, ‚Kommunikation & Kooperation‘, ‚PriMaMedien: Lernen, Lehren und Forschen mit digitalen Medien‘, ‚Frühe mathematische Bildung‘ sowie ‚Lehrkräftebildung‘ intensiv mit aktuellen Forschungs- und Praxisfragen auseinander. Die zentralen Inhalte der Arbeitsgruppen sind in diesem Band ebenfalls dokumentiert.

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)

„Fotos, die jede:r kennt“ Eine empirische Untersuchung historischer Kenntnisse anhand von Bildikonen bei Studierenden des Lehramts Geschichte - Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Geschichtsdidaktisch intervenieren. Beiträge zur Forschungswerkstatt „Geschichtsdidaktik Empirisch“ 2020)

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Geometric-phase metalens to be used for tunable optical tweezers in microfluidics - Geromel, René; Rennerich, Roman; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Geometric-phase dielectric meta-lenses made of silicon with high numerical aperture and short focal lengths are fabricated and characterised. For circularly polarised light, the same meta-lens can act as a converging or diverging lens, depending on the handedness of the circular polarisation. This effect enables application for optical tweezers that trap or release µm-size polymer beads floating in a microfluidic channel on demand. An electrically addressable polarisation converter based on liquid crystals may be used to switch between the two states of polarisation, at which the light transmitted through the meta-lens is focused (trapping) or defocussed (releasing), respectively.

Luminescent DNA-origami nano-rods dispersed in a lyotropic chromonic liquid crystal - Zhang, Bingru; Nguyen, Linh; Martens, Kevin; Heuer-Jungemann, Amelie; Philipp, Julian; Kempter, Susanne; Rädler, Joachim O.; Liedl, Tim; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Wolf Schmids Idealgenetisches Modell der narrativen Ebenen im Kontext eines handlungs- und produktionsorientierten Literaturunterrichts - Schulte Eickholt, Swen (Erzähltheorie(n) im Literaturunterricht. Verhandlungen eines schwierigen Verhältnisses)

Fluchterfahrung. Mahi Binebine, Luiz Ruffato und Friedrich Christian Delius im Vergleich - Schulte Eickholt, Swen (Postkoloniale Germanistik und Konflikte im globalen Kontext)

Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann.

Der Neue Weltengarten. Jahrbuch für Literatur und Interkulturalität 2022

Probleme des Kulturbegriffs der inter und transkulturellen Literaturwissenschaft - Schulte Eickholt, Swen (Interkulturelle Kontellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

KI-basierte Extrahierung von Anforderungen aus Regularien für die Automobilentwicklung - Gräßler, Iris; Özcan, Deniz; Preuß, Daniel (Design fox X - Beiträge zum 34. DfX-Symposium)

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)

Poster: Towards Practical Brainwave-based User Authentication - Fallahi, Matin; Arias Cabarcos, Patricia; Strufe, Thorsten (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

Simone Atangana Bekono: Salomés Zorn (NL: Confrontaties) - Lammer, Christina

Sichtbarer Euklid? Zur Geometrisierung des Bildes in "De pictura" - Siemoneit, Johannes Gabriel (Leon Battista Alberti, "De pictura" (lat.). Kunsttheorie – Rhetorik – Narrative / Teoria dell'arte, retorica, narrative)

Die Zacher-Epitome. Änderungen, Erweiterungen, Auslassungen - Siemoneit, Johannes Gabriel (Der lateinische ›Alexanderroman‹ des Iulius Valerius)

Leon Battista Alberti: "Descriptio urbis Romae". Überlegungen zu Modernität und Entstehungskontexten, nebst lateinisch-deutscher Edition - Siemoneit, Johannes Gabriel

Gegenwartsprotestantismuskunde. 50 Jahre Liturgische Nacht. Katharina Herrmann: Gesungene Katechese. Kommunikation durch Popularisierung. Kulturelle Repräsentationen eines engagierten protestantischen Christentums im Neuen Geistlichen Lied (Religion in der Bundesrepublik Deutschland 11), Mohr Siebeck: Tübingen 2021, 412 S. - Schroeter-Wittke, Harald (Praktische Theologie)

DP-NMT: Scalable Differentially-Private Machine Translation - Igamberdiev, Timour; Vu, Doan Nam Long; Künnecke, Felix; Yu, Zhuo; Holmer, Jannik; Habernal, Ivan

LaCour!: Enabling Research on Argumentation in Hearings of the European Court of Human Rights - Held, Lena; Habernal, Ivan

Worship. Vor 300 Jahren erklang Bachs Magnificat - Schroeter-Wittke, Harald (Praktische Theologie)

Cryogenic reverse flow forming of AISI 304L - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Workpiece property-control permits the application-oriented and time-efficient production of components. In reverse flow forming, for example, a control of the microstructure profile is not yet part of the state of the art, in contrast to the geometry control. This is, due to several reasons, particularly challenging when forming seamless tubes made of metastable austenitic stainless AISI 304L steel. Inducing mechanical and/or thermal energy can cause a phase transformation from austenite to martensite within this steel. The resulting α’-martensite has different mechanical and micromagnetic properties, which can be advantageous depending on the application. For purposes of local property control, the resulting α’-martensite content should be measured and controlled online during the forming process. This paper presents results from the usage of a custom developed cryo-system and different application strategies to use liquid nitrogen as a coolant for local enhancement of the forming-temperature depending α’-martensite content.

La Belgique à travers les textes – Potenziale des sprachlichen und soziokulturel¬len Wissenserwerbs - Bürgel, Christoph; De Knop, Sabine (Belgien – anregend anders: Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)

Rendez-vous à quelle heure ? Kommunikativer Transfer von Uhrzeiten in einen Verabredungsdialog - Bürgel, Christoph (Der Fremdsprachliche Unterricht Französisch)

Et maintenant, faites un dialogue ! Dialogisches Sprechen optimal fördern - Bürgel, Christoph (Der Fremdsprachliche Unterricht Französisch)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.
Keywords: Materials Chemistry; General Chemistry

Coming of Age in Umbruchzeiten der ‚alten Bundesrepublik‘, komplementär: Ulrich Woelks „Der Sommer meiner Mutter“ (2019) und Christoph Peters‘ „Dorfroman“ (2020) - Elit, Stefan (Werke im Dialog. (Virtuelle) Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

Lebendige Anschauung auf Abwegen. Komische Kunstbetrachtungen in Ingo Schulzes Band „Tasso im Irrenhaus“ und Frank Witzels Van-Reuningen-Texten - Elit, Stefan (Werke im Dialog. Virtuelle Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

Monitoring the evolution of dimensional accuracy and product properties in property-controlled forming processes - Stebner, Sophie Charlotte; Arian, Bahman; Martschin, Juri; Dietrich, Stefan; Feistle, Martin; Hütter, Sebastian; Lafarge, Rémi; Laue, Robert; Li, Xinyang; Schulte, Christopher; Spies, Daniel; Thein, Ferdinand; et al. (Electrical Engineering: Systems and Control)

Zusammenarbeit von Frühförderung und Kita im Förderschwerpunkt Sehen - Jesuthasan, Jonitta

Australien und Neuseeland als Projektionen des Südens in deutschsprachiger Gegenwartslyrik von Jan Wagner und Ulrike Almut Sandig - Elit, Stefan (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Reflections on Music in Fiction: Rose Tremain’s Music and Silence (1999), Julian Barnes’s The Noise of Time (2016) and Roger Scruton’s Perictione in Colophon (2000) - Mildorf, Jarmila (Anglia)

Introduction: Abstract Reflection in Contemporary Fiction - Haekel, Ralf; Butter, Stella; Mildorf, Jarmila (Anglia)

Abstract Reflection in Contemporary Fiction (Anglia)

A study on the effects of normalized TSP features for automated algorithm selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Theoretical Computer Science)
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) nearest neighbor relationships of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-nearest neighbor graphs (NNG) of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. A proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.
Keywords: Feature normalization; Algorithm selection; Traveling salesperson problem

Untersuchung der UVC-Bestrahlung als Oberflächenvorbehandlungsmethode von Polycarbonaten zur Erzeugung einer Verbundhaftung zu Flüssigsilikonkautschuken - Hartung, Michael

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of the influence of process and screw configurations on fiber length for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of shear rates in twin-screw extruder using CFD-simulation - Malatyali, Hatice; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

"English was British". Reflecting on language in a globalized world through an excerpt from Naoise Dolan’s novel Exciting Times - Janzen, Thomas; Methfessel, Annette (Englisch betrifft uns)

Influence of fiber geometry and sizing on glass fiber breakage - Bürenhaus, Franziska Isabelle; Moritzer, Elmar (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Meta-Reinforcement-Learning-Based Current Control of Permanent Magnet Synchronous Motor Drives for a Wide Range of Power Classes - Jakobeit, Darius; Schenke, Maximilian; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

"Belgische Literatur in deutscher Übersetzung. Ein Interview mit der Übersetzungswissenschaftlerin Anja Van de Pol-Tegge" (PODCAST) - Huybrechts, Yves

"Vlaanderen Feest! - Der flämische Feiertag 2023" (VIDEO) - Huybrechts, Yves

Österreich zwischen Vorbildfunktion und Eigeninteresse. Der Fall Jever, 1737-1739 - Huybrechts, Yves (Konkurrenzen in der Frühen Neuzeit: Aufeinandertreffen - Übereinstimmung - Rivalität)

Das BelgienNet – ein Portal zu Belgien für die Schule, die Forschung und die breite Öffentlichkeit - Huybrechts, Yves; Karaca, Resul; Thonard, Audrey (Belgien - anregend anders. Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)

Gerd Busse: Typisch Belgisch. België van A tot Z, Eupen: Grenz-Echo Verlag, 2022 - Huybrechts, Yves (Archiv für das Studium der neueren Sprachen und Literaturen)